The movement ALBabiya in Iran - Al-Bayati, Ahmed Kazem Mohsen (Journal of Humanities & Social Sciences, 2019)
In 1844 a religious movement appeared in Iran called by Muhammad Reza al-Shirazi and came with new principles of worship of God different from that of the Prophet Muhammad. This aroused the anger of the clerics who incited the Shah and the general public against the movement that spread in many parts of Iran. After the expansion of the movement began to believe the clerics pose a great threat to the Islamic religion, so there have been calls to demand the need to address them firmly and force, and this makes the Iranian government under Nasser al-Din Shah resort to confront the movement by force, especially after it has weapons and fighters. In these confrontations, the central government decided to liquidate the movement by executing its leader. He was taken to Tabriz and executed with a group of his followers on June 9, 1850, which ended the Babiya but was split into other routes such as Baha’i and Qadaniyah.